2011
DOI: 10.7202/1006346ar
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Career Pipeline: Gender Differences in Pre-Career Expectations

Abstract: Résumé de l'articleLa théorie du pipeline suggère que l'augmentation du nombre de femmes dans les professions dominées par les hommes devrait conduire à davantage d'égalité sur le marché du travail. Cette perspective ne prend toutefois pas en considération les différences d'attentes entre les hommes et les femmes dans le pipeline qui peuvent faire en sorte de perpétuer les iniquités. Cette étude explore les différences dans le choix de la préparation à une carrière, les attentes face à la carrière, et les prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 43 publications
4
44
0
9
Order By: Relevance
“…In addition, Correll (2001Correll ( , 2004 argues that women have downwardly biased self-assessments of their own competences, and these biases are manifested in women's job choices. Although the reasons differ, supply-side theories all suggest that gender segregation will already be evident in the pipeline of people seeking different jobs (Fernandez and Friedrich 2011;Schweitzer et al 2011;Barbulescu and Bidwell 2013). This "limited pipeline" argument has also been used to explain the paucity of women in top positions (Colaco et al 2011;Barsh et al 2012;Parrotta and Smith 2013) and has been reflected in the popular discourse by which women are encouraged to put themselves forward more aggressively and actively compete for senior roles (e.g.…”
Section: Gender Inequality In the Executive Labor Marketmentioning
confidence: 99%
“…In addition, Correll (2001Correll ( , 2004 argues that women have downwardly biased self-assessments of their own competences, and these biases are manifested in women's job choices. Although the reasons differ, supply-side theories all suggest that gender segregation will already be evident in the pipeline of people seeking different jobs (Fernandez and Friedrich 2011;Schweitzer et al 2011;Barbulescu and Bidwell 2013). This "limited pipeline" argument has also been used to explain the paucity of women in top positions (Colaco et al 2011;Barsh et al 2012;Parrotta and Smith 2013) and has been reflected in the popular discourse by which women are encouraged to put themselves forward more aggressively and actively compete for senior roles (e.g.…”
Section: Gender Inequality In the Executive Labor Marketmentioning
confidence: 99%
“…Hamel, 2009;Cech and Blair-Loy, 2010) have identified several barriers facing women in advancing into management roles. At the individual level, genderrole socialisation (Litzky and Greenhaus, 2007;Schweitzer et al, 2011), lower self-efficacy and self-esteem than men (Pell, 1996;Matthews et al, 2010), work/life conflict (Konrad and Cannings, 1997;Coronel et al, 2010), a lack of family and social support (Aycan, 2004), a lack of role models (Sealy and Singh, 2010) and a lack of social capital (e.g. mentors and career sponsors) necessary for advancement (Ragins and Cotton, 1991;Hersby et al, 2009;Metz, 2009) hinder women's advancement into management.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also examine the extent to which the observed gendergroup segregation in the labour market seems to influence students' wage expectations, which in turn can enhance the segmentation process. For example, Schweitzer et al (2011) tested the 'pipeline theory': an increase in the proportion of women in maledominated occupations should reduce the gender gap in pay if women and men in the 'pipeline' expect comparable careers. Using a survey on career expectations among 23,431 Canadian post-secondary students, their findings indicate that even when women have access to more male-dominated jobs, such as in science, engineering, and business administration, the expected wage gap remains high for women and not for men (for the first salary and for the five-year salary).…”
Section: Gender Differences In Wage Expectations: a Literature Reviewmentioning
confidence: 99%
“…According to this perspective, it would seem that women expect higher wages when they imagine progressing within traditionally male-dominated jobs. As Schweitzer et al (2011) point out, analysing the career expectations at the beginning of the pipeline has the advantage of better understanding the performances of students before having experienced a specific discipline socialisation. A contribution to this research is to test the potential impact of these different factors on expected gender gap in pay.…”
Section: Gender Differences In Wage Expectations: a Literature Reviewmentioning
confidence: 99%